JUVENILE DIVERSION BY THE POLICE IN THE PERSPECTIVE OF PANCASILA JUSTICE: REFORMULATION AND OPTIMIZATION (Lex localis - Journal of Local Self-Government, 2025)
Children require special protection, but diversion has not been optimized due to limitations in norms and the repressive approach of law enforcement agencies. Reformulation and optimization based on progressive law and Pancasila justice are necessary so that the judicial system truly protects and restores the future of children. The purpose of this study is to analyze the legal regulations and practices of diversion by police investigators for children in conflict with the law and to formulate a model of reformulation and optimization strategies based on the values of Pancasila justice. This study is a type of normative legal research. The results of the study show that the regulation and practice of diversion by police investigators has not been optimal despite having a normative basis, because it is still limited by the understanding of the authorities, formalistic attitudes, and legal cultural constraints. A reformulation of the law based on the values of Pancasila justice and a progressive approach through substantive discretion, adaptive operational guidelines, and capacity building for officials are needed so that diversion can truly become a means of transformative recovery for children.